Análisis de adopción de nuevas tecnologías para el aumento de la competitividad en la extracción de carbón en el Municipio de Socha - Boyacá (2022)
The present project consists of elaborating a methodological design for the adoption of new technologies in the municipality of Socha, Boyacá, which contemplates a mixed type investigation, by studying qualitative and quantitative variables with descriptive, exploratory and applied approaches; Its methodology is focused on four phases to comply with the established objectives and is based on some activities to be developed; The first phase aims to characterize the coal extraction companies present in the municipality of Socha, in terms of their extraction methods, research capacity and investment in new technologies: the second phase will be to carry out an evaluation identifying the variables that influence the competitiveness of companies and their ability to adopt new technologies, through the application of a data collection instrument, which in this case will be the survey, in the third phase a study of technological surveillance will be carried out, to know with what kind of technologies are counted by companies and in the fourth phase the methodology for the implementation of technology adoption strategies in companies in the municipality of Socha, Boyacá will be designed. Likewise, the concepts of competitiveness and innovation, the importance that the coal mining sector has had in Colombia through the implementation of technologies in the extraction processes and the contribution that coal has in the country's gross domestic product are explained. A period of eight months has been stipulated for this project, for its proper development and will focus mainly on companies in the municipality of Socha, Boyacá. Without less appreciating the other companies in this department, since it is a methodological proposal that can be implemented in any company with extraction and exploitation activities of mineral coal.